Penyelesaian Masalah Pertentangan antara Nas Berasaskan Prinsip Maqasid al-Syari’ah - Hj Ismail, Paizah (Jurnal Fiqh, 2014)
The purpose of this article is to analyse the possibility of using Maqasid al-Syari’ah as a method of solving perceived differences between texts related to any rulings. Amongst Islamic Jurists, this method is usually known as Tarjih Maqasidi, which means using Maqasid al-Syari’ah as a tool or method for solving differences between the said texts. As known by Islamic scholars, Maqasid al-Syari’ah is associated with the concept of bringing benefit (maslahah) and preventing harm (mafsadah). This means using benefit (maslahah) as the basis of acceptance of any deed as well as using harm (mafsadah) as the basis of rejection. Among the key findings of this paper is that what was said by jurists concerning contradiction between the texts is only from the perspective of the scholar, whereas, in fact, it is not. Based on the fact that the confusion arises in the mind of the scholars, the issue can be resolved by referencing to the principles above, which is to bring benefit (maslahah) and prevent harm (mafsadah).